Cytomegalovirus (CMV) Cell-Mediated Immunity and CMV Infection After Allogeneic Hematopoietic Cell Transplantation: The REACT Study - Chemaly, Roy F (Clin Infect Dis, 2020)
BACKGROUND: Cytomegalovirus (CMV) infection remains an important cause of morbidity and mortality in allogeneic hematopoietic cell transplant (allo-HCT) recipients. CMV cell-mediated immunity (CMV-CMI) as determined by a peptide-based enzyme-linked immunospot (ELISPOT) CMV assay may identify patients at risk for clinically significant CMV infection (CS-CMVi). METHODS: The CS-CMVi was defined as CMV viremia and/or disease necessitating antiviral therapy. CMV-CMI was characterized as high when the intermediate-early 1 (IE-1) antigen spot counts (SPCs) were >100 (cutoff 1) or when the IE-1 and phosphoprotein 65 antigen SPCs were both >100 SPCs per 250 000 cells (cutoff 2), and a low CMV-CMI when SPCs were below these thresholds. In this prospective multicenter study, we evaluated CMV-CMI every 2 weeks from the pretransplant period until 6 months posttransplantation in 241 allo-HCT recipients with positive CMV serostatus. The primary endpoint was CS-CMVi occurring within 2 weeks of the last measurement of CMV-CMI. RESULTS: CS-CMVi occurred in 70 allo-HCT recipients (29%). CMV-CMI was low in patients who experienced CS-CMVi (94%), whereas those who had a high CMV-CMI were less likely to have CS-CMVi (P < .0001). Patients with CS-CMVi had higher all-cause mortality (P = .007), especially those with low CMV-CMI (P = .035). On multivariable analysis, CMV-CMI, sex, race, antithymocyte globulin, and steroid use were independent predictors of CS-CMVi, and the time from transplant to engraftment was the only predictor of mortality. CONCLUSIONS: Measurement of CMV-CMI using a novel ELISPOT assay would be useful clinically to monitor allo-HCT recipients and distinguish between those at risk of developing CS-CMVi and requiring antiviral prophylaxis or therapy and those who are protected.